Peran Literasi Keuangan Digital dalam Memitigasi Perilaku Doom Spending: A Narrative Literature Review - Dhiptya Ratri Anggraheni (Universitas Islam Balitar, 2025)
The emergence of the doom spending phenomenon is triggered by anxiety and uncertainty about the future, particularly during crises such as pandemics or economic instability. However, the literature addressing the mitigation of doom spending through digital financial literacy remains very limited. Previous studies have primarily focused on traditional financial literacy without considering its digital components. This article presents a novel approach by integrating digital financial literacy, including access to information, application evaluation, and risk management, as a tool to mitigate doom spending. Using a narrative literature review approach, this study examines the relevance of Behavioral Finance Theory, Protection Motivation Theory, and Theory of Planned Behavior to understand the relationship between digital financial literacy and the transformation of impulsive thinking into rational financial decision-making. The analysis reveals that digital financial literacy plays a crucial role in enhancing perceived behavioral control, reducing the risks of destructive spending, and strengthening individuals’ financial resilience. This study also recommends longitudinal research to evaluate the long-term impact of digital financial literacy, as well as interdisciplinary explorations integrating social and cultural factors in the mitigation of doom spending. These findings offer significant new insights for policymakers, financial practitioners, and academics to address the challenges of the digital economy in the future.